Characterizing intra‐axonal water diffusion with direction‐averaged triple diffusion encoding MRI. (4th May 2018) - Jensen, Jens H.; Helpern, Joseph A.
Abstract : For large diffusion weightings, the direction‐averaged diffusion MRI (dMRI) signal from white matter is typically dominated by the contribution of water confined to axons. This fact can be exploited to characterize intra‐axonal diffusion properties, which may be valuable for interpreting the biophysical meaning of diffusion changes associated with pathology. However, using just the classic Stejskal‐Tanner pulse sequence, it has proven challenging to obtain reliable estimates for both the intrinsic intra‐axonal diffusivity and the intra‐axonal water fraction. Here we propose to apply a modification of the Stejskal‐Tanner sequence designed for achieving such estimates. The key feature of the sequence is the addition of a set of extra diffusion encoding gradients that are orthogonal to the direction of the primary gradients, which corresponds to a specific type of triple diffusion encoding (TDE) MRI sequence. Given direction‐averaged dMRI data for this TDE sequence, it is shown how the intra‐axonal diffusivity and the intra‐axonal water fraction can be determined by applying simple, analytic formulae. The method is illustrated with numerical simulations, which suggest that it should be accurate for b ‐values of about 4000 s/mm 2 or higher. Abstract : The application of a specific triple diffusion encoding MRI pulse sequence is proposed for estimation of the intrinsic intra‐axonal diffusivity and axonal water fraction in white matter. This sequence includes a primary set of axial diffusion encoding gradients along with an additional set of orthogonal radial gradients. The application of the sequence is illustrated with numerical simulations.